Weaving Development Strategy in Balai Panjang Weaving House as Economic Fulfillment of the Community of Balai Panjang Village, Payakumbuh City, West Sumatra Province - Faridiano; Selvi Kasman; Septriani (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study discusses the strategy of weaving development in Balai Panjang weaving houses as an economic fulfillment of the people of Balai Panjang Village. The purpose of this study is to explain weaving as an economic fulfillment of craftsmen in whose development strategies are needed in overcoming the obstacles that occur. The research method used is qualitative research. Data collection techniques include field observations, interviews, and documentation. The theory used is Malinowski's Theory of Functionalism. Weaving which is used as cultural heritage also helps the economy of the community in Balai Panjang with the availability of job opportunities as craftsmen. Weaving at this time still uses traditional tools in its manufacture, causing several obstacles. Obstacles to weaving development include the difficulty of raw materials, low wages for workers, limited human resources, and the absence of promotion. The Industrial Office as the related agency that accommodates the sustainability of the Balai Panjang weaving house carries out several strategies including the procurement of raw materials, increasing the wages of craftsmen, regenerating craftsmen, and increasing promotion.